Amateur film : meaning and practice, 1927-77 - Nicholson, Heather Norris (Manchester : Manchester University Press, 2012)
This book plunges readers into the world of home movie making and reveals that behind popular perceptions of clichéd family scenes shakily shot at home or by the sea, there is much more to discover. Exploring who, how, where, when and why amateur enthusiasts made and shared their films provides fascinating insights into an often misunderstood aspect of national visual history. This study of how non-professional filmmakers responded to the new possibilities of the moving image, places decades of cine-use into a history of changing visual technologies that span from Edwardian visual toys to contemporary mobile phones. Using northern cine club records, interviews and amateur films, the author reveals how film-making practices ranged from family footage to highly crafted edited productions about local life and distant places made by enthusiasts who sought to 'educate, inspire and entertain' armchair audiences during the early decades of British television.
Making space for a neglected visual history -- The amateur club scene -- The rise of a hobby press -- Family life as fact and fiction -- Local lives and communities -- Gazing at other people working -- An indispensable travel accessory -- Socially engaged filmmaking -- Moving pictures, moving on.
Bibliografija: str. [251]-272.
Kazalo.
Keywords: Amaterski film; Velika Britanija